Differential effects of alendronate and losartan therapy on osteopenia and aortic aneurysm in mice with severe Marfan syndrome - Nistala, Harikiran (Oxford University Press, 2010)
Reduced bone mineral density (osteopenia) is a poorly characterized manifestation of pediatric and adult patients afflicted with Marfan syndrome (MFS), a multisystem disorder caused by structural or quantitative defects in fibrillin-1 that perturb tissue integrity and TGFβ bioavailability. Here we report that mice with progressively severe MFS (Fbn1(mgR/mgR) mice) develop osteopenia associated with normal osteoblast differentiation and bone formation. In vivo and ex vivo experiments, respectively, revealed that adult Fbn1(mgR/mgR) mice respond more strongly to locally induced osteolysis and that Fbn1(mgR/mgR) osteoblasts stimulate pre-osteoclast differentiation more than wild-type cells. Greater osteoclastogenic potential of mutant osteoblasts was largely attributed to Rankl up-regulation secondary to improper TGFβ activation and signaling. Losartan treatment, which lowers TGFβ signaling and restores aortic wall integrity in mice with mild MFS, did not mitigate bone loss in Fbn1(mgR/mgR) mice even though it ameliorated vascular disease. Conversely, alendronate treatment, which restricts osteoclast activity, improved bone quality but not aneurysm progression in Fbn1(mgR/mgR) mice. Taken together, our findings shed new light on the pathogenesis of osteopenia in MFS, in addition to arguing for a multifaceted treatment strategy in this congenital disorder of the connective tissue.